Software architecture : 11th European Conference, ECSA 2017, Canterbury, UK, September 11-15, 2017, Proceedings /: 11th European Conference, ECSA 2017, Canterbury, UK, September 11-15, 2017, Proceedings. (2017) - Unknown
No abstract available